First reports of Grania (Clitellata: Enchytraeidae) from Africa and South America: molecular phylogeny and descriptions of nine new species. (10th February 2016) - Prantoni, Alessandro Lívio; De Wit, Pierre; Erséus, Christer
Abstract : In this article, our knowledge of the geographic distribution of G rania species is expanded by describing seven new species, G rania bekkouchei sp. nov., G rania brasiliensis sp. nov., G rania capensis sp. nov., G rania chilensis sp. nov., G rania cryptica sp. nov., G rania hinojosai sp. nov., and G rania simonae sp. nov., from poorly investigated regions of the Southern Hemisphere, plus two new species, G rania carolinensis sp. nov. and G rania unitheca sp. nov., from off the east coast of the USA. An immature achaetous specimen that we call G rania cf. levis was also included. The newly generated data were combined with a previously published data set in order to update the hypothesis of phylogenetic relationships among G rania species. All new species except G . cryptica sp. nov. are supported by both morphological and molecular data. In addition, we find that G . chilensis sp. nov. is structured in at least four distinct populations along the Chilean coast. The species described from South Africa form a monophyletic clade where two are morphologically indistinguishable but diverging in both mitochondrial and nuclear ribosomal genes, and thus we describe them as different species, G . bekkouchei sp. nov. and G . cryptica sp. nov. Among the North Carolinian species, G . unitheca sp. nov. is indicated as a close relative of G rania monospermatheca Erséus & Lasserre, 1976, and G . carolinensis sp. nov. is indicated as a close relative of G . cf. levis . The updated phylogeny is strongly concordant with geographical species distributions, thus supporting a low level of dispersal within this genus, as has previously been hypothesized. © 2015 The Linnean Society of London